Employment options and challenges for rural households in Malawi: An agriculture and rural employment analysis of the fifth Malawi Integrated Household Survey, 2019/20 - Benson, Todd; De Weerdt, Joachim (International Food Policy Research Institute, 2023)
Malawi has suffered from weak economic growth since its independence in 1964. Over 50 percentof the population live below the poverty line, unable to produce enough or to otherwise obtain suffi cient income to meet all of their basic needs. Poverty is concentrated in rural areas. Smallholder agriculture dominates employment in rural Malawi. However, with continuing population growth, the average landholding size for smallholder farming households is declining, resulting in many being unable to produce sufficient food to meet their own needs. To escape poverty, rural households increasingly must diversify their sources of income, but many lack the human and financial capital to do so. In this report, a detailed examination is provided of the agricultural production, non-farm employment patterns, and overall incomes obtained by farming households across Malawi using data from the fifth Malawi Integrated Household Survey (IHS5), conducted in 2019/20. The analysis demonstrates that most poor farming households will never be able to escape poverty through their farming alone, even with substantially higher crop productivity. Rainfed cropping remains the primary form of agricultural production for farming households in Malawi. While increasing numbers are engaging in irrigated farming during the dry season, the returns from such farming are incon sistent and low. More importantly, off-farm income sources, particularly temporary ganyu wage em ployment, are now critical to the livelihoods of most rural households, particularly those with small cropland holdings. The common assumption that agriculture is at the center of the livelihoods of rural households across Malawi no longer holds. Of equal importance is their ability to obtain suffi ciently remunerative off-farm employment. In developing strategies for rural economic and human development in Malawi, accelerating agricultural production growth, particularly through increased productivity, and increasing the returns to farming are necessary, but incomplete solutions. Equal attention must now be paid to how workers in farming households can also qualify for and obtain good off-farm jobs. Without increases in such employment opportunities, the economies of most rural communities across Malawi are likely to stagnate and poverty will deepen among households living in them.